Boundedness and stability of solutions of some nonlinear differential equations of the third-order (2009)
Sufficient conditions are established for the uniform ultimate boundedness of solutions of a third-order nonlinear differential equation (1). When, p(t,x,x',x")=0, criteria under which all solutions x(t), its first and second derivatives tend to zero as t→∞, are given.